2021
DOI: 10.1038/s41598-021-98368-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory performance and locomotor function of patients with anorectal malformations

Abstract: The aim of this study was to assess whether adolescents following anorectal malformation repair have a decreased cardiorespiratory performance capacity and impaired motor skills. All eligible children treated for ARMs between 2000 and 2014 were invited to participate in a prospective study consisting of a clinical examination, evaluation of Bowel function and Quality of Life, spirometry, spiroergometry and assessment of the motor activity. The results were compared to a healthy age- and sex-matched control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…While fecal and urinary incontinence are predictive of the HRQoL in patients with ARM/HD [ 23 ], physical self-concept and perceived physical attractiveness were largely independent of symptom load according to the Rintala score. This finding matches recent studies where lower scores for locomotor function and exercise capacity [ 13 ], as well as pelvic floor muscle defects [ 17 ] were observed without correlation to bowel symptom load. We conclude that physical activity may improve HrQOL in ARM/ HD patients independent of symptom load or presence of an ostomy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While fecal and urinary incontinence are predictive of the HRQoL in patients with ARM/HD [ 23 ], physical self-concept and perceived physical attractiveness were largely independent of symptom load according to the Rintala score. This finding matches recent studies where lower scores for locomotor function and exercise capacity [ 13 ], as well as pelvic floor muscle defects [ 17 ] were observed without correlation to bowel symptom load. We conclude that physical activity may improve HrQOL in ARM/ HD patients independent of symptom load or presence of an ostomy.…”
Section: Discussionsupporting
confidence: 92%
“…Cardiorespiratory fitness and muscular strength are positively correlated with the HRQoL in children and adolescents, including physical and psychological well-being and perceived health status [ 12 ]. A recent study evaluating sports performance revealed a significantly lower relative performance capacity in children with ARM in spiroergometry, independent of symptom load [ 13 ]. These results corroborate our own findings of subjectively reduced endurance in our patient cohort, independent of Rintala score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of 345 articles identified by the database searches, 49 articles met the inclusion criteria. 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 Most concerned esophageal atresia ( n = 17) and Hirschsprung's disease ( n = 14). None of the articles focused on duodenal atresia or omphalocele.…”
Section: Resultsmentioning
confidence: 99%